2017
DOI: 10.1098/rsif.2017.0005
|View full text |Cite
|
Sign up to set email alerts
|

Inferring stratified parasitoid dispersal mechanisms and parameters from coarse data using mathematical and Bayesian methods

Abstract: Biological invasions have movement at the core of their success. However, due to difficulties in collecting data, medium- and long-distance dispersal of small insects has long been poorly understood and likely to be underestimated. The agricultural release of parasitic hymenoptera, a group of wasps that are critical for biological pest control, represents a rare opportunity to study the spread of insects on multiple spatial scales. As these insects are typically less than 1 mm in size and are challenging to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…The negligible success of landings in strong winds in our simulations is consistent with experiments showing take‐off suppression of parasitoids at wind speed above ~2 m/s or even lower (Messing et al., 1997; Strickland et al., 2017). Another interesting prediction stemming from our simulations is that in higher wind speeds, attracting tiny insects to visual targets can be used to manipulate the drifting of these insects even if they do not actually reach the target (Figure 4f,h‐i).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The negligible success of landings in strong winds in our simulations is consistent with experiments showing take‐off suppression of parasitoids at wind speed above ~2 m/s or even lower (Messing et al., 1997; Strickland et al., 2017). Another interesting prediction stemming from our simulations is that in higher wind speeds, attracting tiny insects to visual targets can be used to manipulate the drifting of these insects even if they do not actually reach the target (Figure 4f,h‐i).…”
Section: Discussionsupporting
confidence: 90%
“…It shows that wasps fly differently in the presence and absence of wind and that their active flight can manipulate flight trajectory relative to the ground, even while drifting in winds that substantially exceed their maximum flight speed. Theoretical models of miniature insect dispersal and host‐parasitoid spatial ecology tend not to include aspects of dispersal in directions that are not in the predominant wind direction (Strickland et al., 2017). The insights from the current study can be used to improve such models by including the active flight of the insects (Cronin & Reeve, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These insects are of significant agricultural, ecological, and economic importance. Thrips are a common agricultural pest [2,3], and parasitoid wasps have the potential for use in biological control of agricultural pests [4,5]. For example, a recent study demonstrated that the successful control of thrips using a small predatory insect resulted in an economic benefit of nearly $60 million in California [6].…”
Section: Introductionmentioning
confidence: 99%
“…If there is as much variability in 348 dispersal distance in these species as in those in experiments using replicated releases, the results 349 based on few observations must be treated with caution. Furthermore, stratified dispersal means 350 that the dispersal estimated from both replicated experimental releases and spread of species 351 introduced for biological control may give different results depending on the spatial scale of 352 sampling (Kristensen et al, 2013;Strickland et al, 2017). 353…”
Section: Density-dependent Dispersal In Aphelinus Asychis and Other P...mentioning
confidence: 99%